Examining Child Victims of Incest in Indonesia: Between the Legal System and Family Dysfunction - Tateki Yoga Tursilarini; Trilaksmi Udiati; Irmawan Irmawan; Sunit Agus Tri Cahyono; Suryani Suryani; Dodi Al Vayed (JURIS (Jurnal Ilmiah Syariah), 2024)
This study aimed at examining the factors causing incest sexual abuse against children in the context of family dysfunction and the legal system. A qualitative approach was used in conducting this research with a case study method of five families who experienced incest violence. Data were collected through in-depth interviews, participatory observation, and the analysis of relevant documents. The research findings showed that family dysfunction, such as divorce and poverty, as well as a lack of understanding and application of moral and religious values, were the main factors causing incest. In addition, the implementation of the law, which was not yet effective, and the absence of comprehensive prevention efforts had worsened the situation. This study emphasizes the need for enforcement of the legal system, family understanding, and community culture to be better at preventing, helping, and ensuring legal certainty to protect the psychology and future of children from incest sexual violence.